Immune Thrombocytopenic Purpura Secondary to Peritoneal Tuberculosis Patient with Anti-Tuberculosis Drug-Induced Liver Injury. A Case Report - Yulistiawati, Fitria; Arfijanto, Muhammad Vitanata (Gaceta Médica de Caracas, 2023)
Introduction: Various haematological abnormalities commonly occur in active tuberculosis (TB) but immune thrombocytopenic purpura (ITP) secondary to extrapulmonary TB is exceedingly rare. Case presentation: We reported an 18-year-old male patient who presented with fever, abdominal pain, and thrombocytopenia. From the physical examination, there was found slight abdominal distention and diffuse tenderness. Peripheral blood smear and Immature Platelet Fraction (IPF) investigations were suggestive of ITP.